2019
DOI: 10.1111/1440-1703.12055
|View full text |Cite
|
Sign up to set email alerts
|

Tardigrades in the city: A review of diversity patterns in response to urbanization

Abstract: In different taxonomical groups, the number of species found in urban environments tends to decline compared to adjacent nonurban environments. It is unclear whether tardigrades also conform to this pattern of diversity decline in cities. Tardigrades are microscopic invertebrates which have been understudied, despite the fact that they are cosmopolitan and found in all types of habitats. Due to their capability to withstand extreme conditions, tardigrades should be able to successfully thrive in urban environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Other general reviews that emerged from our search included invertebrates as a small proportion of the broader urban ecology focus on all wildlife (e.g., Collins et al, 2021) or were limited to meta‐analysis of research on invertebrates that quantified the impact of urbanisation on species (e.g., Fenoglio et al, 2021). As urban invertebrate research has grown to include more taxonomic or functional groups of non‐pest insects, taxon‐specific global reviews have also been compiled, as is the case for tardigrades (delBarco‐Trillo, 2019) and copro‐necrophagous beetles (Ramírez‐Restrepo & Halffter, 2016), which have built a clearer picture of how these taxa are impacted by urban environments. The other reviews we found focused on the responses of specific taxa in particular regions or subject to specific disturbances, or conversely, examined urban systems from the broader perspective of understanding the impacts of land use changes but were not directly linked to understanding the ecology of species and patterns of diversity in urban environments (Table 1; Table S1).…”
Section: Overview Of Findingsmentioning
confidence: 99%
“…Other general reviews that emerged from our search included invertebrates as a small proportion of the broader urban ecology focus on all wildlife (e.g., Collins et al, 2021) or were limited to meta‐analysis of research on invertebrates that quantified the impact of urbanisation on species (e.g., Fenoglio et al, 2021). As urban invertebrate research has grown to include more taxonomic or functional groups of non‐pest insects, taxon‐specific global reviews have also been compiled, as is the case for tardigrades (delBarco‐Trillo, 2019) and copro‐necrophagous beetles (Ramírez‐Restrepo & Halffter, 2016), which have built a clearer picture of how these taxa are impacted by urban environments. The other reviews we found focused on the responses of specific taxa in particular regions or subject to specific disturbances, or conversely, examined urban systems from the broader perspective of understanding the impacts of land use changes but were not directly linked to understanding the ecology of species and patterns of diversity in urban environments (Table 1; Table S1).…”
Section: Overview Of Findingsmentioning
confidence: 99%
“…According to the recent checklist of tardigrades species as per the studies published by Degma and Guidetti in 2023, there are 1464 species, 159 genera and 33 families present currently (Degma et al, 2019;Degma & Guidetti, 2023). The Tardigrada phylum accepted two classes and four orders.…”
Section: Classificationmentioning
confidence: 99%
“…Apart from this, the mechanism behind the physiological adaptations made by tardigrades to survive extreme environmental conditions drives the scientific community to develop products having application in various fields. For instance, a recent study published in 2023, conducted by (Mredha et al, Note: * -indicates changed taxa as for updated checklist by (Degma and Guidetti, 2023) 2023) depicted the development of an extremotolerant glycerogels by studying the tun formation process in tardigrades and taking inspiration from this process. These gels have varied applications in the field of biomedicine, energy storage devices, sensors, and soft robotics.…”
Section: Research Scenario Of Tardigrades In India and It's Ecologica...mentioning
confidence: 99%